Combined signals of scientific and social consensus best mobilize action on societal challenges even if government and industry oppose - Anandita Chakraborty Sabherwal; Gregg Sparkman (Proceedings of the National Academy of Sciences, 2026)
When facing real-world societal challenges, people make decisions about how to act based on multiple, often conflicting messages from various influential stakeholders such as governments, scientists, fellow citizens, and private companies. How does the public decide to act amid potentially converging or diverging signals from multiple entities in society? Which entities remain influential even if other groups appear apathetic or stand in opposition? This question becomes especially important in contexts like the United States where the government, industry, scientists, and public sentiment may diverge. In two conjoint experiments spanning over 40,000 evaluations, one behavioral experiment and a digital field study ( N s = 1,515, 2,005, 1,604, 50,668 respectively; all preregistered), we show the relative and combined influence of government bodies, scientific experts, industry stakeholders, and social consensus in the general public in driving responses to 10 issues in environmental, health, and technology domains. Across domains, support from scientists and social consensus was most influential in shaping the American public’s responses to societal problems including policy support, product preferences, donations to a cause, and social media engagement. And when facing opposition from government and industry, the combined, but not isolated, support of scientists and social consensus reliably mobilized action across domains. This work suggests that even amid rising systemic opposition to solving contemporary societal challenges, scientists and the public can come together to mobilize action.